No reason for identity: on the relation between motivating and normative reasons - Mantel, Susanne (Philosophical explorations, 2014)
This essay is concerned with the relation between motivating and normative reasons. According to a common and influential thesis, a normative reason is identical with a motivating reason when an agent acts for that normative reason. I will call this thesis the ‘Identity Thesis’. Many philosophers treat the Identity Thesis as a commonplace or a truism. Accordingly, the Identity Thesis has been used to rule out certain ontological views about reasons. I distinguish a deliberative and an explanatory version of the Identity Thesis and argue that there are no convincing arguments to accept either version. Furthermore, I point out an alternative to the Identity Thesis. The relation between motivating and normative reasons can be thought of as one of representation, not identity.
Online veröffentlicht: 26. Juli 2013
Gesehen am 23.12.2025